Balancing the imbalance of stroke survivors with backward slope walking on differential treadmill gradients - Elvis l. Agbonhalor; Isoken F. Osagiede (Turkish Journal of Kinesiology, 2019)
The purpose of this study was to balance the imbalance of stroke survivors by using backward slope walking on differential treadmill gradients to challenge the cardiovascular and neuromuscular systems and by synthesizing an analysis of lower limb biomechanics during this task. Thus, a total of thirty (30) stroke survivors randomly drawn participated in this study. Balance and co-ordination were tested in relation to backward slope walking on differential treadmill gradients (0°, 5°, and 10°). Analysis of covariance was used to test the hypotheses at 0.01 level of significance. The F-values of 68.80 and 33.32 for balance and coordination were respectively found to be statistically significant at 0.01. Turkey HSD was used to determine the source of the significant difference among the groups. It was discovered that there was a significant difference at 10° gradient compared to 5° and 0° (10°>5°>0°) in the balance and coordination of the participants. It was therefore recommended that backward slope walking should be used as an additional component in intervention/rehabilitation program to provide cardiovascular fitness, balance control/proprioception by increasing the amount of blood pump at each stroke and the efficiency of the heart of stroke survivors.